Nebulized Normal Saline Solution for Treatment of Bronchial Asthma Exacerbations and Bronchiolitis: Not Standard of Care. (November 2018) - Hassan, Shadwa; Gonzalez, Anthony; Demissie, Seleshi; Morawakkoralage, Kashun; James, Pushpom
Nebulized normal saline is frequently prescribed for the treatment of bronchiolitis or bronchial asthma exacerbations. We aimed to reinforce guidelines care by educating providers on the futility of saline administration. Frequency and indications for nebulized normal saline prescription were documented from November 1, 2014, to April 1, 2015, and then again, after dissemination of educational material to providers, from November 1, 2016, to April 1, 2017. A total of 263 patients had bronchiolitis and 470 had asthma. Nebulized normal saline for bronchiolitis decreased significantly in the emergency department (ED) and inpatient settings ( P < .001 and P = .027, respectively). For asthma exacerbations, the use of nebulized normal saline decreased significantly in the inpatient setting ( P = .025), while in the ED, numbers were low at baseline and remained unchanged. Nebulized normal saline administration in the hospital setting results in continued use in the community, where this leads to unnecessary ED visits, where first-line therapy should have been administered.